2017
DOI: 10.1002/mds.26905
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical dysconnectivity in paroxysmal kinesigenic dyskinesia: Combining functional magnetic resonance imaging and diffusion tensor imaging

Abstract: Thalamomotor/premotor hyperconnectivity suggests abnormal communication between thalamus and motor cortex in patients. Furthermore, thalamoprefrontal hypoconnectivity in proline-rich transmembrane protein 2-mutated patients might indicate that proline-rich transmembrane protein 2 mutations result in inefficient thalamoprefrontal integration. Our findings facilitate a deeper understanding of the crucial role of thalamocortical dysconnectivity in the pathophysiological mechanisms of paroxysmal kinesigenic dyskin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…Similarly, recent studies also substantiated evidence of pathological glutamatergic neurotransmission underlying Tourette's syndrome . Furthermore, there is some evidence suggesting changes in connectivity of certain circuits (cortico‐striato‐pallido‐thalamo‐cortical in tics; thalamomotor‐cortical circuits in PKD with or without PRRT2 mutations) as shared pathophysiological mechanism …”
Section: Discussionmentioning
confidence: 82%
“…Similarly, recent studies also substantiated evidence of pathological glutamatergic neurotransmission underlying Tourette's syndrome . Furthermore, there is some evidence suggesting changes in connectivity of certain circuits (cortico‐striato‐pallido‐thalamo‐cortical in tics; thalamomotor‐cortical circuits in PKD with or without PRRT2 mutations) as shared pathophysiological mechanism …”
Section: Discussionmentioning
confidence: 82%
“…We then executed whole-brain fiber tracking in native diffusion space using the Fiber Assignment by continuous Tracking (FACT) algorithm, which was included in the Diffusion Toolkit ( Liao et al, 2011 ). The cut-off rules of the adopted algorithm were: (1) fractional anisotropy (FA) larger than 1.0, or (2) the angle between the current and the previous path segment exceeded 35 degree ( Long et al, 2017 ). Finally, we co-registered the regions of interest (ROIs) of three major subdivisions of the CC (genu, body and splenium) mentioned above to native diffusion space.…”
Section: Methodsmentioning
confidence: 99%
“…Functional magnetic resonance imaging (MRI) studies have revealed an abnormal connectivity between the thalamus and the motor cortex in patients with PKD, and the functional abnormality is associated with the duration of the disease [37]. In patients with PRRT2 mutations, the thalamo−prefrontal hypoconnectivity has been observed, indicating that the PRRT2 mutations result in inefficient thalamo-prefrontal integration and dysfunction of motor inhibition [38]. Mechanistic studies have also revealed that the core pathogenesis of PKD is the disturbed cell excitability caused by PRRT2 mutation, which is associated with presynaptic dysfunction, abnormal neurotransmitter release and the lack of negative regulation of Na + channels [31,32].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%